Effect of Gender, Age, and Profound Disease on Upper Airway Stimulation Outcomes. (August 2020) - Patel, Jena; Daniels, Kelly; Bogdan, Lauren; Huntley, Colin; Boon, Maurits
Objective: To evaluate treatment outcomes of upper airway stimulation (UAS) in obstructive sleep apnea (OSA) patients based on patient age, gender, and preoperative disease severity. Methods: Retrospective chart review of patients undergoing UAS from 2014 to 2018 at a tertiary care center. Data collected included demographic information, implantation records, and pre- and postoperative polysomnography (PSG) results. Profound OSA was defined as AHI >65 and age ≥65 was considered advanced age. The primary outcome measured was initial treatment response, defined as a post-operative AHI <20 with a >50% reduction from baseline. Results: 145 patients underwent UAS at our institution including 98 males and 47 females with a mean age of 61.7 ± 11.5 years, mean BMI of 29.1 ± 3.9 kg/m 2, and mean preoperative AHI of 34.1 ± 18.2 events/hour. After surgery, patients had a significantly lower mean AHI of 8.6 ± 15.0 events/hour (<0.001). Older patients had a lower initial treatment response rate (78%) when compared to their younger counterparts (94%) ( P = 0.005). Male gender and profound disease status did not significantly impact treatment response rates; young age was the only variable found to predict early treatment response on multivariate analysis ( P = 0.003). Conclusion: Although the overall OSA population showed significant postoperative AHI reduction with UAS, patients age ≥65 years were less likely to have an initial response to treatment, when compared to their younger counterparts. A larger proportion of elderly patients and patients with profound OSA had residual moderate disease (AHI > 15) after UAS. Level of Evidence: 4